Outbreak of carbapenem-resistant enterobacteria in a thoracic-oncology unit through clonal and plasmid-mediated transmission of the blaOXA-48 gene in Southern France - Hadjadj, Linda; Cassir, Nadim; Saïdani, Nadia; Hoffman, Clémence; Brouqui, Philippe; Astoul, Philippe; Rolain, Jean-Marc; Baron, Sophie Alexandra (Frontiers in Cellular and Infection Microbiology, 2022)
Background Carbapenemase-producing Enterobacteriaceae (CPE) represent an increasing threat to public health, especially in hospitals. Objectives To investigate an outbreak of CPE in a thoracic-oncology unit by using whole genome sequencing (WGS) and to describe the control measures taken to limit the epidemic, including fecal microbiota transplantation (FMT). Methods A retrospective study between December 2016 and October 2017 was performed to investigate an outbreak of CPE in a thoracic-oncology unit at the North Hospital in Marseille, France. The isolates were identified, and antimicrobial susceptibility tests were performed. All CPE were sequenced using MiSeq and/or MinIon technologies. Nucleotide variations between plasmids and similarity within the same species were investigated. The origin of this outbreak, its spread, and the decolonization of patients in the ward were also studied. Results Four Citrobacter freundii, one Enterobacter cloacae and four E. hormaechei OXA-48 carbapenemase producers were isolated in eight patients hospitalized the same year in a thoracic-oncology ward. The blaOXA-48 gene was present in a Tn1999.2 transposon located in IncL/M plasmids, with single nucleotide variants (SNV) ranging from 0 to 5. All C. freundii strains belonged to the same ST22 and had more than 99.6% similarity between them. Two strains of E. hormaechei ST1007 were almost identical at 99.98%, while the others belonged to a different ST (ST98, ST114, ST133). No single source was identified. FMT resulted in decolonization in 4/6 patients. Conclusions WGS demonstrated the dissemination of the blaOXA-48 gene by both clonal (C. freundii ST22 and E. hormaechei ST1007) and plasmid spread (pOXA-48 IncL/M). The origin of this outbreak appeared to be both external and internal to the ward. This evidence of cross-infection supports the urgent need for the implementation of infection control measures to prevent CPE dissemination.